ASSESSMENT OF BIOLOGY AND MORPHOMETRIC CHARACTERISTICS OF DIFFERENT STAGES OF LEAFHOPPER, AMRASCA BIGUTTULA BIGUTTULA (ISHIDA) ON OKRA - B. JAYARAO; SOMASEKHAR; B. ABDUL KHADAR; L. KRISHNA NAIK; M. M. VINAYKUMAR (The Bioscan, 2015)
Okra is an economically important vegetable crop grown in tropical and sub-tropical parts of the world. Among many destructive pests of okra, leafhoppers are undoubtedly more severe. Studies on biology and morphometric characteristics of Amrasca biguttula biguttula (Ishida) were conducted under laboratory conditions during 2011- 12 at University of Agricultural Sciences, College of Agriculture, Raichur. The incubation period lasts for 6.55 ± 0.40 days. The duration of first, second, third, fourth and fifth nymphal instars were 6.55, 1.67, 1.27, 1.33, 1.67 and 2.10 days, respectively. The total nymphal period was 8.04 ± 0.51 days. The male and female had longevity of 16 and 18 days respectively, with a total fecundity of 17.53 ± 0.52 per female. The life cycle ranged from 15 to 18 days.